Optimal Collusion with Internal Contracting - LEE, Gea Myoung (Institutional Knowledge at Singapore Management University, 2008)
In this paper, we develop a model of collusion in which two firms play an infinitelyrepeated Bertrand game when each firm has a privately-informed agent. The colluding firms, fixing prices, allocate market shares based on the agent’s information as to cost types. We emphasize that the presence of privately-informed agents may provide firms with a strategic opportunity to exploit an interaction between internal contracting and market-sharing arrangement: the contracts with agents may be used to induce firms’ truthful communication in their collusion, and collusive market-share allocation may act to reduce the agents’ information rents.